Potensi Produk Hasil Pengelolaan Peternakan Sapi Perah Kampung Nagrak Desa Sukajaya Lembang - Ellin Harlia; Yuli Astuti; Eulis Tanti Marlina (Media Kontak Tani Ternak, 2023)
Community service (PPM) integrated with Unpad Community Service Program (KKN) has been carried out from January 2023 to March 2023 in Nagrak Village, Sukajaya Village, Lembang District, West Bandung Regency. Activities carried out with Unpad KKN students are dairy farm waste management, dairy cattle environmental sanitation, and greening and processing milk into products to support dairy farming activities. The purpose of PPM activities is to improve the ability of Obor group member families to manage dairy farm waste to create a sanitary farm environment to obtain milk that meets SNI requirements. The Obor group has processed farm waste into vermicompost, briquette fertilizer, biogas, and biocompound. The method used during PPM is participatory from Obor family members through counseling, technical guidance, and implementation of organic fertilizer products for sunflower and vegetable plants, milk processing into caramel, yogurt, and milk sponge by involving UNPAD KKN students. The results of PPM activities obtained by Obor members have managed dairy farm waste, then utilized it, and some have been sold. The obstacles faced are time and labor.Key words: waste, animal husbandry, dairy cattle, extension, technical guidance